Nano-silica particles synergistically IgE-mediated mast cell activation exacerbating allergic inflammation in mice - Yang, Yong-Shi; Cao, Meng-Da; Wang, An; Liu, Qing-Mei; Zhu, Dan-Xuan; Zou, Ying; Ma, Ling-Ling; Luo, Min; Shao, Yang; Xu, Dian-Dou; Wei, Ji-Fu; Sun, Jin-Lyu (Frontiers in Immunology, 2022)
Background: Allergic respiratory diseases have increased dramatically due to air pollution over the past few decades. However, studies are limited on the effects of inorganic components and particulate matter with different particle sizes in smog on allergic diseases, and the possible molecular mechanism of inducing allergies has not been thoroughly studied. Methods: Four common mineral elements with different particle sizes in smog particles were selected, including Al2O3, TiO2, Fe2O3, and SiO2. We studied the relationship and molecular mechanism of smog particle composition, particle size, and allergic reactions using mast cells, immunoglobulin E (IgE)-mediated passive cutaneous anaphylaxis (PCA) model, and an ovalbumin (OVA)-induced asthmatic mouse model in vitro and in vivo, combined with transmission electron microscopy, scanning transmission X-ray microscopy analysis, and transcriptome sequencing. Results: Only 20 nm SiO2 particles significantly increased β-hexosaminidase release, based on dinitrophenol (DNP)-human serum albumin (HSA) stimulation, from IgE-sensitized mast cells, while other particles did not. Meanwhile, the PCA model showed that Evan’s blue extravasation in mice was increased after treatment with nano-SiO2 particles. Nano-SiO2 particles exposure in the asthmatic mouse model caused an enhancement of allergic airway inflammation as manifested by OVA-specific serum IgE, airway hyperresponsiveness, lung inflammation injury, mucous cell metaplasia, cytokine expression, mast cell activation, and histamine secretion, which were significantly increased. Nano-SiO2 particles exposure did not affect the expression of FcεRI or the ability of mast cells to bind IgE but synergistically activated mast cells by enhancing the mitogen-activated protein kinase (MAPK) signaling pathway, especially the phosphorylation levels of the extracellular signal-regulated kinase (ERK)1/2. The ERK inhibitors showed a significant inhibitory effect in reducing β-hexosaminidase release. Conclusion: Our results indicated that nano-SiO2 particles stimulation might synergistically activate IgE-sensitized mast cells by enhancing the MAPK signaling pathway and that nano-SiO2 particles exposure could exacerbate allergic inflammation. Our experimental results provide useful information for preventing and treating allergic diseases.